IMPLEMENTASI EVALUASI MODEL KIRKPATRICK PADA PROGRAM PELATIHAN TEKNIK TERHADAP GURU PENDIDIKAN AGAMA ISLAM DI SMP - Muh. Anwar HM; Mania, Sitti; Mawardi, Amirah (Department of Islamic Education Management, 2023)
The increase in teacher professionalism is marked by an increase in the competencies that must be owned by teachers, namely pedagogic competencies related to managing students, social competencies related to communication skills and professional competencies related to the ability to master knowledge and improve the quality of learning while studying. The practice of prayer is a skill that must be cultivated by the teacher. Teachers teaching junior high school students need to be creative in their approach to teaching, engage and motivate their students. Make practice with clear details. If you have material about prayer with clear pictures and interesting details, students are always happy when the teacher takes the time to explain how to pray in great detail. Knowing the proper prayer procedures, a teacher must have a deep understanding and be skilled in using various techniques and have a good stage performance which usually displays magical elements and is intended for the benefit of the student himself. This is then passed down from generation to generation. They usually have magical or supernatural elements and often teach Islamic religious teachings.